2020
DOI: 10.1371/journal.pone.0234744
|View full text |Cite
|
Sign up to set email alerts
|

Salt inducible kinases as novel Notch interactors in the developing Drosophila retina

Abstract: Developmental processes require strict regulation of proliferation, differentiation and patterning for the generation of final organ size. Aberrations in these fundamental events are critically important in tumorigenesis and cancer progression. Salt inducible kinases (Siks) are evolutionarily conserved genes involved in diverse biological processes, including salt sensing, metabolism, muscle, cartilage and bone formation, but their role in development remains largely unknown. Recent findings implicate Siks in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…In addition, it has also been shown that induced activation of oncogenic Ras and Src in the Drosophila eye epithelia resulted in small benign tumors, however when co-expressed with Sik2-CA resulted in tumor overgrowth ( Hirabayashi and Cagan, 2015 ). A study by Şahin et al (2020) showed complex genetic interactions including potent synergy of Sik2 and Sik3 with a Notch-based tumor model. These results demonstrate that like the results of this study, different oncogenic mutations can synergise to produce tumor overgrowths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has also been shown that induced activation of oncogenic Ras and Src in the Drosophila eye epithelia resulted in small benign tumors, however when co-expressed with Sik2-CA resulted in tumor overgrowth ( Hirabayashi and Cagan, 2015 ). A study by Şahin et al (2020) showed complex genetic interactions including potent synergy of Sik2 and Sik3 with a Notch-based tumor model. These results demonstrate that like the results of this study, different oncogenic mutations can synergise to produce tumor overgrowths.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research in Drosophila has found that Sik2 and Sik3 are upstream regulators of the Hippo signalling pathway, a conserved pathway that is vital for controlling organ size, and Sik2 can increase Yki target gene expression and promote tumorigenesis ( Wehr et al, 2013 ; Hirabayashi and Cagan, 2015 ). Siks were also found to mediate tumorigenesis via Notch signaling in a combinatorial cancer model involving overexpression of the Notch ligand Delta and loss of chromatin modifiers ( Şahin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A loss of crystal cells was also seen upon the ubiquitous but not the hemocyte-specific induction of Gskt and Sik2 S1032A . The former shares similarities with GSK3 kinase, a core component of the Wnt signaling pathway, whereas the latter regulates energy homeostasis as well as Notch signal transduction [57,69,70]. Hence, both may have a more general role in proliferation and development.…”
Section: Influence Of Ubiquitous and Hemocyte-specific Induction Of S...mentioning
confidence: 99%